Investigation about quality in the Brazilian aerospace industry - Souza, J. P.E.; Alves, J. M.; Silva, M. B. [UNESP] (My University, 2011)
This paper has as purpose to investigate the main characteristics of the quality improvement programs used in the organizations of the aerospace industry in Brazil. This theme is extremely relevant in the scenery of the actual aerospace industry, seeing that the organizations of this sector invest in quality improvement programs and have difficulties in evaluating the strategic effect in the quality of its products and/or services. The methodology used was a quantitative research conducted as a survey, where the universe of the collected data consisted in organizations of the aerospace sector, where the obtained answers of the collected data, by an electronic questionnaire, were analyzed and organized to make it possible the analysis of the data. Concluding the paper the findings of the research are presented.
Keywords: Aerospace; Brazil; Improvement; Programs; Quality; Survey